Use of Cerebrospinal Fluid Biomarkers in Diagnosis and Monitoring of Rheumatoid Meningitis - Nissen, Mette Scheller; Nilsson, Anna Christine; Forsberg, Jonatan; Milthers, Jesper; Wirenfeldt, Martin; Bonde, Christian; Byg, Keld-Erik; Ellingsen, Torkell; Blaabjerg, Morten (Frontiers in Neurology, 2019)
Rheumatoid meningitis is a rare extra-articular manifestation of rheumatoid arthritis, often with non-specific symptoms. In most cases brain MRI shows a patchy lepto- and pachy meningeal enhancement, but the diagnosis currently relies on examination of a meningeal biopsy with presence of plasma cells and rheumatoid noduli. Presence of IgM rheumatic factor (RF) has been found in several cases and recently two cases have shown high titer anti-cyclic citrullinated peptide (anti-CCP) in CSF, suggesting this as a potential marker for rheumatoid meningitis. We present a 62-year-old woman with sero-positive (RF IgM and anti-CCP) rheumatoid arthritis, presenting with headache and gait impairment. Brain MRI revealed the classical patchy meningeal enhancement and the diagnosis of rheumatoid meningitis was confirmed by neuropathological examination of a meningeal biopsy. Analysis of the CSF revealed positive RF IgM (92.7 IU/mL) and strongly positive anti-CCP (19600 IU/mL) and CXCL-13 (>500 ng/L). After treatment with high-dose steroid and Rituximab the clinical symptoms resolved. A 6-month follow-up analysis of CSF showed a dramatic decrease in these all markers with negative RF IgM and a decrease in both anti-CCP (64 IU/mL) and CXCL-13 (<10 ng/L). Our case further underlines the potential use of CSF anti-CCP and RF IgM in the diagnosis of RM and the use of these markers and CXCL-13 in evaluation of treatment response.